2020
DOI: 10.1021/acscatal.0c00414
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Site-Mediated Hydrogenation Catalysis on Pd/NiO: Selective Biomass Transformation and Maintenance of Catalytic Activity at Low Pd Loading

Abstract: Creating a new chemical ecosystem based on platform chemicals derived from waste biomass has significant challenges: catalysts need to be able to convert these highly functionalized molecules to specific target chemicals and they need to be economicalnot relying on large quantities of precious metalsand maintain activity over many cycles. Herein, we demonstrate how Pd/NiO is able to direct the selectivity of furfural hydrogenation and maintain performance at low Pd loading by a unique dual-site mechanism. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 54 publications
7
40
0
Order By: Relevance
“…From product distribution plots as a function of reaction time or conversion (Figure 2 and Figure S.3) it appears clear that the FF is preferentially hydrogenated to THFA over Ir/NiO at all time points and at each FF conversion value, thus indicating that a different pathway is followed over this catalyst compared to Ir/CeO 2 and Ir/TiO 2 . Furthermore, the peculiar behaviour of Ir/NiO is in line with what has been already observed over NiO and Pd/NiO [34] …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…From product distribution plots as a function of reaction time or conversion (Figure 2 and Figure S.3) it appears clear that the FF is preferentially hydrogenated to THFA over Ir/NiO at all time points and at each FF conversion value, thus indicating that a different pathway is followed over this catalyst compared to Ir/CeO 2 and Ir/TiO 2 . Furthermore, the peculiar behaviour of Ir/NiO is in line with what has been already observed over NiO and Pd/NiO [34] …”
Section: Resultssupporting
confidence: 89%
“…The reason behind the peculiar selectivity of Ir/NiO could be a result of the unique capacity of the NiO support to adsorb and activate the furfural molecule, as already reported for Pd/NiO catalysts [34] …”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The conversion to acetals requires Brønsted acid sites on the TiO 2 surface [61,62] . We recently published an article on Pd/NiO catalysts and were able to demonstrate a dual‐site hydrogenation mechanism, where spillover of hydrogen onto the NiO support was a significant part of the reaction pathway [63] . For TiO 2 , hydrogen spillover creates surface hydroxyls that are able to act as Brønsted acid sites required for ether formation [64,65] .…”
Section: Resultsmentioning
confidence: 99%
“…Campisi et al reported that Pd/NiO can catalyze the selective conversion of furfural to tetrahydrofurfuryl alcohol (72%), although Pd/TiO 2 favours furfuryl alcohol (68%). 2 Furfural is regarded as a promising platform molecule to various products in a biorefinery. Its selective conversion using tailored catalysts is desired.…”
Section: Selective Hydrogenationmentioning
confidence: 99%